Steinert's disease, from assumption to certainty in neurological practice (Balneo and PRM Research Journal, 2022)
Steinert’s disease or myotonic dystrophy type 1 (MD1), is the most prevalent myopathy in adults. We report the case of a pacient who was admitted to the Neurology Department for the progressive decrease in muscle strength in the lower limbs bilaterally. Symptoms began about 18 months before the presentation to the Neurology Department. On the electroneurographic examination, specific features for myotonic dystrophy type 1 were described, confirmed later by the genetic examination.